Valorizing meat by-products for human consumption: understanding consumer attitude formation processes - Lavranou, Georgia; Henchion, Maeve; McCarthy, Mary B.; O’Reilly, Seamus J. (Frontiers in Animal Science, 2023)
A considerable body of research work has identified that meat by-products contain significant amounts of high-quality protein, which when properly extracted can lead to valuable opportunities for the food industry. However, market success of food products containing protein extracted from meat by-products is subject to consumer acceptance. This study explores Irish consumers' attitudes towards hypothetical food products containing protein derived from beef offal sources. A nationally representative survey (n=953) was undertaken to investigate what attitude processes, intuitive and/or deliberate, dominate attitude formation towards food products containing beef offal derived protein while accounting for the effects of product familiarity and information provision. The study reveals that consumers’ both intuitive and deliberate evaluations worked in the same direction, predicting overall attitudes towards these products. Deliberate evaluation was found to be a better predictor of consumers’ attitudes than intuitive evaluations. Consumers’ perceived familiarity with the product concepts positively influenced their deliberate evaluations. Consumers who received benefit information about the health and environmental consequences of consuming food products containing protein extracted from beef offal expressed a more positive deliberate attitude towards these products. The current research demonstrated that consumers expressed relatively positive attitudes towards the food products containing protein extracted from beef offal, with protein extracted from familiar offal sources having better potential to be accepted by consumers in Ireland. The findings have implications for new product development, and more generally for strategies that seek to ensure sustainable food production and consumption.